MENINGKATKAN MINAT BACA MELALUI PERMAINAN TEKA TEKI SILANG DAN âBALSEM PLANGâ - Wirahyuni, Kadek (ACARYA PUSTAKA, 2017)
In the learning process, reading is something a must to do. There are many ways to increase interest in reading, including with crossword puzzles (TTS) and âbalsam plangâ or five minutes reading before going home. TTS can be categorized as a stimulant that serves to manage stress and connect the sleeping nerves of the brain. The nature of